Persistence of folly : on the origins of German dramatic literature - Lande, Joel B. (Ithaca, NY : Cornell University Press and Cornell University Library, 2018)
"Persistence of Folly revises the conventional literary-historical narrative of German theater (and literature) through the lens of the stage fool. Including original interpretations of Goethe's Faust (1808) and Kleist's Broken Jug (1811), this study considers how the stage fool was reworked and redeployed over two centuries, helping to create a German literature of world-historical rank"--Provided by publisher
The fool at play -- Fabricating comedy and fate of the fool in the age of reform -- Life, theater, and the restoration of the fool -- The vitality of folly in Goethe's Faust and Kleist's Jug.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 06, 2018).
JSTOR
Keywords: German drama -- Early modern, 1500-1700 -- History and criticism; German drama -- 18th century -- History and criticism; Fools and jesters in literature; German drama (Comedy) -- History and criticism; Théâtre allemand -- 18e siècle -- Histoire et critique; Fous et bouffons dans la littérature.; Comédie allemande -- Histoire et critique; DRAMA -- Continental European; HISTORY -- Europe -- Germany; Fools and jesters in literature; German drama; German drama (Comedy); German drama -- Early modern; 1500-1799; Criticism, interpretation, etc